Nano titanium oxide for modifying water physical property and acid-resistance of alluvial soil in Yangtze River estuary - Jili Qu (De Gruyter, 2021)
This study aims to investigate the role of nano TiO2 in modifying the characteristics of Shanghai clayey silt – alluvial soil in Yangtze river estuary. The Shanghai clayey silt is first mixed with nano TiO2 with different size group and content before it is made to undergo liquid and plastic limit tests, standard Proctor compaction tests, and acid-resistant tests. The results show that nano TiO2 can substantially increase the liquid limit and plastic limit of TiO2-treated clayey silt, but can decrease the plasticity index of it to some degree. The result from standard Proctor compaction tests shows that the maximum dry bulk density (MBD) decreases and the optimum water content (OWC) increases compared with untreated samples. Acid-resistance of sample is significantly increased after being treated by nano titanium dioxide. The data provided by this study can be used for not only the soil and water conservation, but also for soil improvement, diversity of vegetables and animals, amelioration of crop land, as well as sustainable development.